1985
DOI: 10.1159/000469363
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Alloxan Diabetes and Insulin Treatment on the Activity of Alanine Aminotransferase in Rat Brain Regions, Liver and Heart

Abstract: Studies with brain alanine aminotransferase showed higher activity of the enzyme in the soluble fraction of cerebellum. Among the tissues, the liver soluble fraction was the richest source of the enzyme. Alloxan-induced diabetes caused both regional and timedependent variations in the activity of brain alanine aminotransferase. Significant among these changes were the decrease in both soluble and particulate enzyme from cerebral hemispheres and an increase in the soluble enzyme activity from cerebellum at earl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1986
1986
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…[ 19,20 ] Despite this, the brain tissue showed higher activity of the transaminases and AST in the soluble fraction of the cerebellum. [ 49 ] In the current research, we found that the brain AST and ALT activities of diabetic animals significantly increased in comparison to non‐treated rats. The decreased brain tissue transaminase activities in diabetics treated with VOL were observed to be even lower than that of the normal group rats.…”
Section: Discussionmentioning
confidence: 51%
“…[ 19,20 ] Despite this, the brain tissue showed higher activity of the transaminases and AST in the soluble fraction of the cerebellum. [ 49 ] In the current research, we found that the brain AST and ALT activities of diabetic animals significantly increased in comparison to non‐treated rats. The decreased brain tissue transaminase activities in diabetics treated with VOL were observed to be even lower than that of the normal group rats.…”
Section: Discussionmentioning
confidence: 51%
“…Myocardial alanine levels have been shown to increase in experimental model of diabetes (Scharff and Wool 1966). Furthermore cardiac activity of alanine aminotransferase increases in diabetes (Kazmi and Baquer 1985) and seems to predict coronary heart disease events (Schindhelm et al 2007). In the non-diabetic CAD patients, alanine was significantly higher in the LV compared to RV (Figure 2B).…”
Section: Discussionmentioning
confidence: 99%